Investigations on characteristics of Shugor, Dubasi and Watish ewe lambs at first lambing at El Huda sheep research station - Sulieman, A.H.; Ali, H.O.; Jack, E.E. El (1985)
Investigation on characteristics of 26 Shugor, 21 Dubasi and 16 Watish ewe lambs at first lambing at El Uda sheep research station in Sudan was conducted. The mean values for weight include being highest for Shugor with 42.8±1.63kg Dubasi 41.5±1.42kg and least for Watish 35.6±1.29kg. There is an apparent overall ewe age effecter on mean birth weight. There is a negative significant association of weaning weight and average per-weaning daily gain with that of lambing age in the Shugor. Like will there was a significantly negative relationship between overall rate of growth to lambing and the age of ewe lamb at the respective time within the Dubasi.